Total synthesis of propolisbenzofuran B - Srinivas, Kolluru; Ramana, Chepuri V. (Organic Letters, 2017)
An efficient synthesis of propolisbenzofuran B, which possesses promising anticancer activity, is reported. The key cyclohexanone framework of this tricyclic natural product has been constructed employing a Rh-catalyzed intramolecular olefin hydroacylation. The requisite key olefin intermediate was synthesized by using gold-catalyzed allenyl ether [1,3] O -> C rearrangement.